Corpus Delicti : London i 90'erne. - Behmdt, Helle; Christensen, Torben; Renton, Andrew (Kobenhavn : Kunstforeningen, 1995)
Bulloch, Angela ; Chapman, Dinos ; Chapman, Jake ; Collishaw, Mat ; Fairhurst, Angus ; Gussin, Graham ; Lane, Abigail ; Lucas, Sarah ; Starr, Georgina ; Taylor-Wood, Sam ; Wilson, Louise ; Wilson, Jane
biografie
Corpus Delicti : London i 90'erne, Kunstforeningen, Kobenhavn, 25. marts - 28. maj 1995
Engels & Deens
boek
Keywords: London